Treatment of Antibiotic Pharmaceutical Wastewater Using a Rotating Biological Contactor - Rongjun Su; Guangshan Zhang; Peng Wang; Shixiong Li; Ryan M. Ravenelle; John C. Crittenden (Journal of Chemistry)
Rotating biological contactors (RBC) are effective for treating wastewater, while they are rarely reported to be used for treating antibiotic pharmaceutical wastewater (APW). The current study investigates treatment of APW using an RBC. The effects of influent concentration, number of stages, and temperature on the remediation of APW were studied. The results indicated, even at low ambient temperature, 45% COD and 40% NH4+-N removal efficiencies. Moreover, the BOD5 removal efficiency was 85%. Microscopic observations illustrated that there were various active microorganisms displayed in the biofilms and their distribution changed from stage to stage. Compared with activated sludge, the biofilms in this study have higher content of dry matter and are easier to dehydrate and settle. Compared with current commercial incineration processes or advanced oxidation processes, RBC can greatly reduce the treatment cost. This research shows RBC is effective for such an inherently biorecalcitrant wastewater even at low ambient temperature.